1998
DOI: 10.1016/s0022-5347(01)63093-3
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterisation of the Dendritic Cell Infiltrate in Prostate Cancer

Abstract: This is the first time that DC have been studied in prostate cancer using the relatively new DC specific monoclonal antibodies CD83 and CMRF-44. These findings suggest that there is no active recruitment of DC into prostate cancer and those DC present are only minimally activated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(58 citation statements)
references
References 21 publications
2
55
1
Order By: Relevance
“…3 However, the majority of treated prostate cancer patients were resistant to DC-based immunotherapies, suggesting that this approach should be further improved. 8 As it has been shown, DC numbers decrease in prostate cancer tissues in comparison to benign prostatic hyperplasia (BPH) tissues 24 and the levels of infiltrating DC further decreases with the increase of anaplastic grade. 25 Our previous experiments demonstrated that prostate cancer cells induced apoptosis of human DC during the in vitro co-incubation.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, the majority of treated prostate cancer patients were resistant to DC-based immunotherapies, suggesting that this approach should be further improved. 8 As it has been shown, DC numbers decrease in prostate cancer tissues in comparison to benign prostatic hyperplasia (BPH) tissues 24 and the levels of infiltrating DC further decreases with the increase of anaplastic grade. 25 Our previous experiments demonstrated that prostate cancer cells induced apoptosis of human DC during the in vitro co-incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the cytokine milieu encountered in tumors, DCs can either mediate anti-tumor activity or support tumor growth and metastasis. In fact, increasing evidence from analyses of human ovarian, breast, prostate and renal cell carcinoma reveals the presence of tumor-promoting rather than tumor-suppressing dendritic cells, and altered dendritic cell function and differentiation is likely to be one of the most fundamental mechanisms by which tumors escape immune responses [231][232][233][234][235]. Pro-tumorigenic dendritic cells can favor metastasis by inducing tumor immunotolerance and by promoting tumor angiogenesis.…”
Section: Nks and Dcsmentioning
confidence: 99%
“…Tumor cells, TAMs and tumoral immunosuppressive T cells can secrete high amounts of VEGF-A, IL-6, macrophage colony-stimulating factor (M-CSF), COX2, IL-10, TGFb and gangliosides, which suppress maturation of DCs [192]. Most myeloid DCs found in human ovarian, breast, prostate and renal cell carcinoma are therefore immature and may induce tumor immunotolerance [231][232][233][234]. Tumor-secreted IL-10 and VEGF also induce expression of B7-H1 on myeloid dendritic cells, a ligand for PD-1 receptor expressed on suppressor T cells [238].…”
Section: Nks and Dcsmentioning
confidence: 99%
“…Dendritic cells (DCs) also play an important role in both the activation of antigen-specific immunity and the maintenance of tolerance, providing a link between innate and adaptive immunity. Several clinical studies have reported the presence of DC within human tumours such as the stomach, colon, prostate, kidney, thyroid, breast and melanoma (Tsujitani et al, 1990;Enk et al, 1997;Troy et al, 1998;Bell et al, 1999;Lespagnard et al, 1999;Schwaab et al, 1999Schwaab et al, , 2001Scarpino et al, 2000). However, the effect of such an infiltration in tumour progression is still not clear.…”
Section: Macrophagesmentioning
confidence: 99%
“…However, the effect of such an infiltration in tumour progression is still not clear. Some of these studies have shown that the infiltration of DC was associated with enhanced patient survival (lung), whereas others showed that DC present in tumour either were minimally activated (Tsujitani et al, 1990;Troy et al, 1998), had no correlation with metastasis-free or overall survival of the patients (Lespagnard et al, 1999) or were converted to 'silencers' of antitumour immune responses by tumour-produced factors (Enk et al, 1997). In addition, studies have reported that patients with a variety of cancers have impaired function of DCs, indicating a systemic effect of the tumours on DCs (Almand et al, 2000).…”
Section: Macrophagesmentioning
confidence: 99%